Kerukunan Umat Beragama Dikalangan Peserta Didik Pada Sekolah Menengah Kejuruan Negeri 9 Medan - Afifah Adilah; Muhammad Yunan Harahap (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
Finding out what kind of religious peace exists among SMK Negeri 9 Medan students was the driving force for this research.  Although the majority of the student body is Muslim, this public school does include some Christian, Catholic, and Buddhist pupils as well.  A descriptive strategy is used in this qualitative investigation.  Interviews, documentation, and observation were the methods used to gather data.  The data analysis followed the steps outlined by Miles and Huberman, which include reducing the data, presenting the data, and making conclusions.  What came out of study entitled "Religious Harmony among Students of SMK Negeri 9 Medan" are that students from various religious backgrounds are able to live in harmony and respect each other. Although the majority are Muslim, there is no discrimination against minority students. They can interact and work together in various school activities without imposing their will or beliefs. This shows that the values of local wisdom and tolerance are still well maintained in the school environment.